Biblical interpretation in ancient Israel - Fishbane, Michael, 1943- (Clarendon Press ; Oxford Univ. Press, 1985)
An award-winning study which analyzes the phenomenon of textual analysis in ancient Israel, exploring the tradition of exegesis prior to the development of biblical interpretation in early classical Judaism and the earliest Christian communities.